A review on region of interest-based hybrid medical image compression algorithms - Suhaila Ab Aziz; Suriani Mohd Sam; Norliza Mohamed; Salwani Mohd Daud; Siti Zaleha Abdul Rashid; Hafiza Abas; Muhammad Fathi Yusof; Rudzidatul Akmam Dziyauddin (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
Digital medical images have become a vital resource that supports decision-making and treatment procedures in healthcare facilities. The medical image consumes large sizes of memory, and the size keeps on growth due to the trend of medical image technology. The technology of telemedicine encourages the medical practitioner to share the medical image to support knowledge sharing to diagnose and analyse the image. The healthcare system needs to ensure distributes the medical image accurately with zero loss of information, fast and secure. Image compression is beneficial in ensuring that achieve the goal of sharing this data. The region of interest-based hybrid medical compression algorithm plays the parts to reduce the image size and shorten the time of medical image compression process. Various studies have enhanced by combining numerous techniques to get an ideal result. This paper reviews the previous works conducted on a region of interest-based hybrid medical image compression algorithms.